(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This paper examines the challenges that lexical gaps and cultural lacunas pose in the process of translation. Lexical gaps refer to the absence of an equivalent word in the target language, while cultural lacunas are the result of missing cultural concepts that cannot be directly translated without explanation or adaptation. These issues are especially relevant in cross-cultural communication where languages reflect different worldviews, traditions, and values. The article explores typologies of lexical gaps, the nature of cultural lacunas, strategies for bridging these gaps, and the impact of sociolinguistic and pragmatic context in resolving translational mismatches.